Aktualisasi Total Quality Management dalam Meningkatkan Profesionalisme Guru di Lembaga Pendidikan Islam - Risnita Risnita; Fahrina Yustiasari Liriwati (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
The task of the teacher to give instructions and guide students for more progressive in their knowledge, skills and self-constructivity to develop their potential. The teacher carries out his duties requiring technical skills that are supported by certain personality attitudes, and are guided by a code of ethics at the institution where he works, especially in Islamic education institutions. Technical skills, personality attitudes, obedience to religious values ​​should develop when teaching profession is supported, and the situation provides opportunities in a professional manner, and teacher can realize the vision and mission of teaching and simultaneously carry out the vision and targets of the educational institutions in which they work. Increased professionalism of teachers requires Total Quality Management (TQM) which aims to encourage management to work in total to improve quality, quality assurance and provide satisfaction to customers; parents, students themselves and other stakeholders. This paper will outline the role of TQM in increasing the professionalism of teachers in Islamic education institutions